Doctors' Spouses and Doctors as Spouses - Myers, Michael F. (1986)
The personal and working lives of physicians and their spouses have changed markedly over the past ten to 15 years. Dual career marriages are now quite common. Spouses often have concerns about their physician spouses' overwork, depression, alcohol and drug use, parenting, difficulty in communicating, sexuality, attitude towards money, and about marital separation. Physicians have similar concerns about their spouses' mood changes and drug use, communication problems, dependency, needs for understanding and affection, and about separation. Marital therapy is an effective, time-efficient, and humane way to treat physicians and their spouses during times of marital distress.